Feminism in the “Little Women” Movie Reviewed from The Aspects of Career, Love and Independence - Yulia Tria Hapsari (English Research Journal : Journal of Education, Language, Literature, Arts and Culture, 2020)
This study concerned about the feminism that showed in the movie entitled “Little Women” especially from the aspects of career, love and independence. The objectives of the study were: 1) to describe career, love and independence of the women in the 19th century that represented in “Little Women” movie; 2) to describe the woman perception towards career, love, and independence in the 19th century as seen in “Little Women” movie; 3) to describe Jo March’s struggle in achieving her dreams in career, love and independence; 4) to describe the impact of gender equality in teaching and learning process in school. The method of the research used was descriptive qualitative research. The data collection used was documentation technique. Interactive model data of analysis used to analyze the data. The result of this study showed that: 1) upper-class women were more ideal compared to middle-class women in the 19th century from men’s point of view; 2) in the 19th century, most of the women were inclined with men’s point of view about ideal women; 3) Jo March represented the woman in the 19th century that succeeded in achieving her dreams in career, love and independence; 4) Gender education is important thing to be taught to the students in any level of schools. Keywords: Feminism, Movie, Career, Love, Independence